2012
DOI: 10.1084/jem.20120325
|View full text |Cite
|
Sign up to set email alerts
|

Antibody orientation at bacterial surfaces is related to invasive infection

Abstract: Bacterial surface proteins switch the orientation of IgG binding depending on the antibody concentration of their environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
114
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 51 publications
16
114
0
3
Order By: Relevance
“…Pre-adsorption of PG to Pt sensor surfaces enhances the specific binding of the Fc region of mammalian IgG [3]. This oriented attachment of antibody [5] [7] serves to expose the Fab region, which maximizes the tethering capability for immunoprecipitation of antigens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-adsorption of PG to Pt sensor surfaces enhances the specific binding of the Fc region of mammalian IgG [3]. This oriented attachment of antibody [5] [7] serves to expose the Fab region, which maximizes the tethering capability for immunoprecipitation of antigens.…”
Section: Resultsmentioning
confidence: 99%
“…The physiologic function of this Fc:PG binding serves to facilitate bacterial infection and avoidance of the host's immune system by nonspecifically coating bacteria with host antibodies [6]. Antibodies bound to PG are oriented with the antigen specific binding pockets facing outwards, away from the pathogen [5] [7]. This ability to specifically bind antibodies aligned in a precise orientation has been utilized to develop antibody-based detection systems [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon contrasts with labeling of bacteria with IgG antibodies upon cleavage by IdeS. Björk et al showed that IgG Fab fragments remain attached to the bacterial surface upon IgG cleavage [28]. We propose that the detachment of IgM F(ab’)2 fragments is due to the lower affinity of IgM binding [29].…”
Section: Discussionmentioning
confidence: 96%
“…The combination of MS methods facilitated the categorization of the interacting proteins into groups that specifically bind to the surface of S. pyogenes at high concentrations. Applying these methods to a strain that caused both asymptomatic pharyngitis and invasive disease within the same patient, 24 demonstrates the importance of interactions between S. pyogenes and human plasma proteins for the transition from mild to severe infection. The results also underline that the combination of mass spectrometry based techniques can improve our current understanding of molecular interactions that contribute to bacterial virulence, a knowledge that has the potential to identify novel opportunities to treat patients with invasive infections.…”
Section: Introductionmentioning
confidence: 99%
“…The results also underline that the combination of mass spectrometry based techniques can improve our current understanding of molecular interactions that contribute to bacterial virulence, a knowledge that has the potential to identify novel opportunities to treat patients with invasive infections. An M1 strain isolated from asymptomatic pharyngitis (in the throat) and from necrotic tissue (in the leg) of the same patient 24 was also investigated. Single colonies were grown to exponential phase in 30g/L Todd--Hewitt broth (BD) and 6g/L yeast extract (Merck, Darmstadt, Germany) (THY), harvested by centrifugation and resuspended in 20mM Tris--HCl(Merck), 150mM NaCl (Sigma--Aldrich, St. Louis, MO, USA), pH 7.6, to a concentration of 2x10 9 CFU/ml.…”
Section: Introductionmentioning
confidence: 99%